Galatians 3: 1 as an Allusion to Textual Prophecy - Wendt, Heidi (Journal of Biblical literature, 2016)
As he admonishes the Galatians for their alleged sympathy to a different gospel, Paul makes a curious statement in 3:1b about having visually portrayed Jesus Christ crucified while among them. The meaning of the clause hinges on the sense of the verb .... Despite an exact parallel in Rom 15:4 in reference to prophecies "forewritten" in the Judean writings, an overwhelming scholarly consensus construes this clause as "to proclaim or exhibit publicly" and, in turn, views it as an illustration of Paul's vivid rhetorical style. This interpretation has a long history but has gained further support in recent decades, as numerous Pauline scholars have argued for the apostle's familiarity with conventions of classical rhetoric. I argue, however, that the verse's immediate and wider context supports a predictive rendering of the key verb and also that this sense has in the past been excluded on questionable grounds that anticipate its rhetorical framework. Rather, I consider 3:1b an important piece of evidence for the role of textual practices within Paul's religious program, one that aids in situating him amid a broader phenomenon of divination from ostensibly prophetic literary corpora as well as a particular class of religious activity.